Load Balancing in Cloud Computing System - Sharma, Rashmi; Kumar, Abhishek (Asian Journal of Electrical Sciences, 2012)
The conception of Cloud computing has not only reshaped the field of distributed systems but also fundamentally changed how businesses potential extend today. Load balancing is a core and challenging issue in Cloud Computing. How to use Cloud computing resources efficiently and gain the maximum profits with efficient load balancing algorithm is one of the Cloud computing service providers’ ultimate goals. In this paper firstly a analysis of different Virtual Machine (VM) load balancing algorithms was done a new VM load balancing algorithm has been proposed and Implemented in Virtual Machine environment of cloud computing in order to achieve better response time.